IDENTIFIKASI KHAT DAN ALIRAN TAREKAT BERDASARKAN INSKRIPSI PADA KOMPLEKS MAKAM RAJA-RAJA TURIKALE, MAROS, SULAWESI SELATAN - Rosmawati, Rosmawati (JURNAL ILMU BUDAYA, 2021)
The focus of this research is the aspects of the past that are transmitted from the inscription data on the Turikale Maros Tomb Complex. The problem posed is what types of khat are used and what Islamic orders are adopted based on the inscription data in the Turikale Maros Tomb Complex. The research data were six tombs containing 14 inscription panels in the Turikale Maros Tomb Complex. The results of this study indicate that the inscription data contains Al-Quran verses, prayers, tauhid sentences, names of characters and time of death written in three khat styles, namely khat Kufi, Nashk, and Tsulust. This study concludes that the dominant Khat is the Tsulust khat because it is more effective in the use of carving and its aesthetic aspects that are more prominent, and the flow of the tarekat adhered to by the Turikale royal court is the Qadiriyah Order.